Políticas de ação afirmativa para negros no governo Fernando Henrique Cardoso (1995-2002) - Paula, Marilene de (2010)
This work’s intention is to show through the analysis of the political configuration on racial relations in Brazil in the late 1990’s and beggining of this century that a new and specific field of public policies has been launched: the promotion of racial equality. In order to achieve this goal, I examine the creation and the development of several affirmative action programs started under Fernando Henrique Cardoso’s governorship (1995-2002), which were spread through many Ministries, such as Justice, Agricultural Development, Education, Foreign Affairs, Work and also in the higher Brazilian court, Supremo Tribunal Federal, so that we have the chance to understand the meaning and the effects of those policies and also of the official speech that helped to increase the debate on racial relations in our country.